STAKEHOLDERS MAPPING IN OVERCOMING CHILD MARRIAGE PROBLEMS IN SEMARANG - Damarjati Prabowo; Dewi Rostyaningsih (Journal of Public Policy and Management Review, 2019)
The handling of children's marital needs more attention from the government of Semarang City. The unpreparedness of reproductive organs at the age of children affected the BBLR even death during childbirth. It is important to know the role of stakeholders in the Semarang City in resolving children's marital problems. The purpose of this research is to know the characteristics that are owned by stakeholders and categories and stakeholders efforts in Semarang city in addressing the problem of children's marital. This research used a qualitatively descriptive method. The results showed the characteristic of stakeholders are to reject children's age marriage, although there are still stakeholders who cannot resist. The indicators used are important indicators, r esources, channels, possible participation, level of influence, implications and action. Stakeholders who reject the child's marriage is the office of Population Control and family planning, the Office of Women Empowerment and child protection, Office of Health, Office of Education, Sub-district, PPT light of Love and the equivalent foundation. While the stakeholders who can not refuse the children’s marital are Department of Population and Civil registration, the Office of the Ministry of Religious Affairs, Courts of Religion and society. Suggested advice: The Department of Population Control and family planning is to program the handling of children’s marriage and coordinate them with related agencies. The Women Empowerment and child Protection Office prioritizes the handling in the form of Perda, The Health office: to strengthen the socialization of reproductive health, The Education office: instructs the planting value of anti-marital children to school, The district need to prioritize the handling of children's age wedding during Musrenbang, PPT light of Love must be given the authority for the prevention of Children’s Marital, the equivalent foundation of regulation, the Office of Ministry of Religion needs to running programs Directly to the public, The Religious Court need to complicates the marriage and public dispensations to attempt to make it aware of its surroundings not to marry at the age of the child.